The framework for athletes to win in and outside of the classrooms :retiring from sports: a challenge - Crispim, Guilherme Goulão Ribeiro (2022)
This project pretends to analyze the difficulties faced by student-athletes when having dual careers. We included the good practices done by exemplar countries ,and then comparing it with our country’s student-athletes. While analyzing the dual careers, it is important to understand that there’s a life after sports, and it is sometimes a challenge for athletes who are in transition. With that it was possible to conclude that having a dual career and preparing the sports retirement is fundamental to succeed not only during the sports’ career, but also after that.